MANAJEMEN PRODUKSI NAUPLIUS UDANG VANAME (Litopenaeus vannamei) DI INSTALASI PEMBENIHAN UDANG BALAI PERIKANAN BUDIDAYA AIR PAYAU, GELUNG, SITUBONDO, JAWA TIMUR - Sandi Afrianto; Abdul Muqsith (Samakia : Jurnal Ilmu Perikanan, 2014)
The purpose of this study was to determine the production management nauplius vaname shrimp in Shrimp Hatchery Installation Brackish water Aquaculture Centres, Gelung, Situbondo. this research use descriptive method, primary data were collected by interviews and direct observation in the field. From these results it can be concluded that in the production of nauplius vaname shrimp (Litopenaeus vannamei), there are several stages, among others, includes the preparation container and media maintenance, procurement and parent selection, transporting, feeding management, water quality management, ablation, processes gonadal maturation, broodstock spawning, nesting and hatching harvesting and packaging. In general, production activities nauplius vaname Installation Shrimp Hatchery Brackish Water Aquaculture Centres in accordance with SOP.